Validity of the 1966 Tax Model as a Research Tool. - Copeland, Ronald M.; Moore, Michael L. (The Accounting Review, 1972)
Abstract This article presents information on the validity of the 1966 tax model and its effectiveness as a research tool. The Internal Revenue Service expects that the 1966 Model will aid researchers in measuring the impact of proposed changes code. The description manual accompanying the model states that, the Individual Tax Model is primarily a research tool that will accurately test hypotheses regarding income, deductions, tax base, tax rates, or any combination of these factors. This paper reports on a validity check on the data underlying the tax model. Specifically, they were concerned with concurrent validity, that is, investigation of the relationship of one set of data to an alternate accepted contemporary measure of the same underlying phenomenon. Tax researchers often desire data on the average dollar amount of an informational item categorized by Adjusted Gross In come (AGI) class. For example, researchers may be interested in the average amount of salaries and wages, dividends, property taxes and so forth, for categories of taxpayers broken down by AgI classes.